Pre-Feasibility Evaluation of the Eco-Cooler Model Made of Waste for Hot Humid Climates - Pratiwi, Niniek; Ernawati (Universitas Negeri Gorontalo, 2023)
Based on the results of a survey conducted by the Ministry of Energy and Mineral Resources in 2018 on commercial buildings, the largest energy-using equipment of each commercial building is air conditioning equipment with an average energy use of over 62%. Therefore, energy-saving efforts related to space cooling will have a significant impact on energy-saving efforts in the world. One way is to use the wind catcher method, namely Eco-Cooler. On the other hand, based on data from the National Waste Management Information System in 2021, waste generation in Indonesia reached 30,881,803.15 tons per year. So this research aims to find the lightest eco-cooler material that can withstand the weather using composite materials from waste. This research uses an experimental method by making an eco-cooler prototype using processed waste materials such as wood powder, corn cobs, plastic, and sand. Then 2 types of sizes, namely the outlet diameter (D1A) of 40 cm, and the inlet diameter (D2A) of 20 cm, while the second size is the outlet diameter (D1B) is 30 cm, and the inlet diameter (D2B) is 15 cm. After molding, the eco-cooler was then weighed and observed for a month to see its resistance to weather where the weather at that time was quite fluctuating. The parameters tested in this study were material weight and weather strength in the humid tropical climate. From the results of this study, it is found that the eco-cooler with sawdust material has the lightest weight of 16 kg for a diameter of 40 cm and 15 kg for a diameter of 30 cm. Meanwhile, the heaviest material is sand with a weight of 29 kg for a diameter of 40 cm and 23 kg for a diameter of 30 cm. In terms of durability, sawdust and sand are the most resistant to weather. Therefore, it can be concluded that the lightest and most weather-resistant eco-cooler material for hot humid climates is eco-cooler from wood powder material.